Internet financial reporting in Turkey - (:unkn) unknown (Emerald Group Publishing Ltd., 2011)
Purpose – This paper aims to investigate internet financial reporting following major regulatory changes in Turkey. Although these regulations only cover publicly listed firms, large unlisted firms also use the internet to disseminate financial information. Design/methodology/approach – The study surveys the top 500 Turkish industrial firms on the “Istanbul Chamber of Industry 500” (ICI500) to determine whether the regulatory changes led to significant changes in their financial reporting on the internet. Findings – The percentage of firms providing financial disclosures on the internet doubled from 2003 to 2010. However, problems remain, including the extremely low level of voluntary disclosures (six percent of firms) and the failure of listed firms to provide information other than mandatory disclosures such as financial summaries and ratios. The study finds increases in voluntary disclosures of share price performance and management reports, providing support for the signaling theory. Originality/value – This study investigates listed as well as unlisted firms and specifically addresses the consequences of regulatory intervention. © Emerald Group Publishing Limited.
Keywords: Financial reporting; Internet financial reporting (IFR); Mandatory disclosures; Regulatory intervention; Turkey; Voluntary disclosures